Effect of foreknowledge on neural activity of primary “go” responses relates to response stopping and switching - Xu, Benjamin; Levy, Sarah; Butman, John; Pham, Dzung; Cohen, Leonardo G.; Sandrini, Marco (Frontiers in Human Neuroscience, 2015)
Being able to stop (or inhibit) an action rapidly as in a stop-signal task is an essential human ability. Previous studies showed that when a pre-stimulus cue warned of the possible need to stop a response in an upcoming trial, participants’ response time (RT) increased if the subsequent trial required a “go” response (i.e., “go” RT cost) relative to a trial where this uncertainty was not present. This increase of the “go” RT correlated with more efficient response stopping. However, it remains a question whether foreknowledge of upcoming inhibition trials given prior to the task is sufficient to modulate neural activity associated with the primary “go” responses irrespective of whether stopping an overt response is required. We presented three task conditions with identical primary (i.e., “go”) response trials but without pre-stimulus cues. Participants were informed that Condition 1 had only “go” trials (All-go condition), Condition 2 required a “stop” response for some trials (Stop condition), and Condition 3 required a response incongruent with the primary response (i.e., Switch response) for some trials (Switch condition). Participants performed the tasks during functional magnetic resonance imaging (fMRI) scans. Results showed a significant increase in the “go” RT (cost) in the Stop and Switch conditions relative to the All-go condition. The “go” RT cost was correlated with decreased inhibition time. fMRI activation in the frontal-basal-ganglia regions during the “go” responses in the Stop and Switch conditions was also correlated with the efficiency of Stop and Switch responses. These results suggest that foreknowledge prior to the task is sufficient to influence neural activity associated with the primary response and modulate inhibition efficiency, irrespective of whether stopping an overt response is required.